Sound and Noise : A Listener's Guide to Everyday Life - Epstein, Marcia Jenneth (McGill-Queen's University Press, 2020)
A timely evaluation of the noise that surrounds us, how we hear it, and what we can do about it, Marcia Jenneth Epstein gives us the impetus and the tools to understand the sounds and noise that define our daily lives. This is a groundbreaking interdisciplinary study of how auditory stimuli impact both individuals and communities.